Toward a Holistic Approach to Sustainable Development : A Guide to Integrated Land-Use Initiatives - World Bank (World Bank, Washington, DC, 2021)
Through the Sustainable Development Goals (SDGs), the international community has recognized the need for an approach to development that considers the interdependence of human and natural systems. Single-sector approaches to development challenges are insufficient to produce sustainable landscapes that promote resilience and help communities mitigate and adapt to climate change. Achieving sustainable development requires stakeholders to work together to minimize trade-offs and increase synergies between different, and often competing, sector-focused goals. Integrated land use initiatives offer a holistic approach to addressing complex environmental and development challenges. This approach seeks to sustainably manage multiple land uses across landscapes, considering both the natural and human systems that depend on them. The objective of this report is to take stock of lessons learned, document best practices from a range of integrated land use initiatives, facilitate knowledge sharing, and provide a guide for practitioners who are looking to implement this approach. This report provides a basic toolkit for practitioners and raises awareness of the cutting-edge work happening in this space.